Phase Equilibrium Study in Supercritical Fluid Extraction of Ethanol to Octane Mixture Using CO2 - Davarnejad, R; Kassim, K.M.; Zainal, A; Sata, Suhairi A. (ASEAN Journal of Chemical Engineering, 2007)
Solubility data was measured for carbon dioxide with ethanol and octane using a phase equilibrium loading re-circulating high-pressure type apparatus at a pressure up to 100.75 bar and a temperature of 348.15K for ethanol and octane mixture involved with 25% ethanol and 75% octane. Experimental data was compared with the calculated regular solution theory data. A procedure is employed to each phase by applying activity coefficient expressions based on regular solution theory. Calculations along these lines are described and the physical bases for applying this method under the relevant conditions are discussed. The regular solution theory approach has been found to be encouraging for the prediction of phase equilibria solubilities though the interaction parameters must be regarded as pressure dependent.